Cellulose kraft pulp reinforced polylactic acid (PLA) composites: effect of fibre moisture content - Elias Retulainen; Kirsi Immonen; Lisa Wikström; Upi Anttila; Sanna Virtanen (AIMS Materials Science, 2016)
PLA offers a competitive and CO2 neutral matrix to commonly used polyolefin polymer based composites. Moreover, the use of PLA reduces dependency on oil when producing composite materials. However, PLA has a tendency of hydrolytic degradation under melt processing conditions in the presence of moisture, which remains a challenge when processing PLA reinforced natural fibre composites. Natural fibres such as cellulose fibres are hygroscopic with 6–10 wt% moisture content at 50–70% relative humidity conditions. These fibres are sensitive to melt processing conditions and fibre breakage (cutting) also occur during processing. The degradation of PLA, moisture absorption of natural fibres together with fibre cutting and uneven dispersion of fibres in polymer matrix, deteriorates the overall properties of the composite. In the given research paper, bleached softwood kraft pulp (BSKP) reinforced PLA compounds were successfully melt processed using BSKP with relatively high moisture contents. The effect of moist BSKP on the molecular weight of PLA, fibre length and the mechanical properties of the composites were investigated. By using moist never-dried kraft pulp fibres for feeding, the fibre cutting was decreased during the melt compounding. Even though PLA degradation occurred during the melt processing, the final damage to the PLA was moderate and thus did not deteriorate the mechanical properties of the composites. However, comprehensive moisture removal is required during the compounding in order to achieve optimal overall performance of the PLA/BSKP composites. The economic benefit gained from using moist BSKP is that the expensive and time consuming drying process steps of the kraft pulp fibres prior to processing can be minimized.